Administration of commensal Shewanella sp. MR-7 ameliorates lipopolysaccharide-induced intestine dysfunction in turbot (Scophthalmus maximus L.). Issue 102 (July 2020) - Zhang, Beili; Li, Chaoqun; Wang, Xuan; Liu, Chengdong; Zhou, Huihui; Mai, Kangsen; He, Gen
Abstract: This study was designed to evaluate whether the administration of commensal Shewanella sp. MR-7 (MR-7) could ameliorate lipopolysaccharide (LPS)-induced intestine dysfunction in turbot. Fish (body weight: 70.00 ± 2.00 g) were randomly divided into three groups including the control group treated with dough, the LPS group treated with dough plus LPS, and the LPS+MR-7 (LMR) group treated with dough plus LPS and MR-7. These three groups with 24 fish each were force-fed with 1 g dough daily for 7 continuous days. The results revealed that MR-7 administration ameliorated LPS-induced intestinal injury, showing higher intestinal villus and microvillus height. Further results showed that MR-7 could inhibit LPS-induced activation of TLR-NF-κB signaling thus maintaining the normal expression levels of cytokines and finally ameliorate the intestinal inflammatory response in turbot. Compared with the LPS group, LMR group had less goblet cells and lower mucin-2 expression level. Moreover, MR-7 restored LPS-induced down-regulation of tight junction protein-related gene expression ( zonula occluden-1, occludin, tricellulin and claudin-3 ). Further investigations indicated that MR-7 partially counteracted LPS-induced changes in gut microbiota composition, enhanced the beneficial bacteria Lactobacillus and reduced the Pseudomonas, thus maintaining the overall microbiota balance. Taken together, the administration of MR-7 could effectively restore LPS-induced intestine function disorder in turbot by ameliorating inflammatory response, mucosal barrier dysfunction and microbiota dysbiosis. Highlights: Intestinal repair potential and mechanism of Shewanella sp. MR-7 in aquatic animals were evaluated for the first time. Shewanella sp. MR-7 ameliorated lipopolysaccharide-induced intestinal inflammation and mucosal barrier dysfunction in turbot. Shewanella sp. MR-7 restored lipopolysaccharide-induced intestinal microbiota dysbiosis in turbot. Commensal Shewanella sp. MR-7 plays beneficial role in improving the host gut health.